Bagaimana Pengasuhan Spiritual Mampu Membangun Karakter yang Baik pada Remaja Muslim? - Yuliana Intan Lestari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Building good character is an important effort for adolescents, especially Muslim adolescents with a background in their values. But this is not easy without the role of care given by parents in the family. This study aims to examine how spiritual parenting in the family is able to build good character in Muslim adolescents. Participants in this study was 200 people. The research data was obtained using psychological scales, namely the spiritual parenting scale and the good character scale. Data of this study was analysed by using product moment correlation technique. The results of the analysis showed a significant relationship between spiritual parenting and good character in Muslim adolescents with (r) correlation = 0.412 (p = 0.000). Its means that the increasing of the spiritual parenting can make a good character in them. This illustrates that success in building a solid foundation in the formation of good character in adolescents can not be separated from the important role of parents in providing patterns of spiritual parenting in adolescents.